SFP selection algorithm for SFC - Yongqing ZHU; Xia GONG; Huanan CHEN (Dianxin kexue)
In order to achieve the new business deployment model by the convergence of cloud and network,SFC technology has been promoted greatly.As one of the key technologies in SFC,the SFP selection strategy affects the network performance and business experience directly.Aiming at the single target defect existing in business path se-lection strategy,the minimum weight algorithm based on the network delay and load was proposed and simulated.It could optimize the resources allocation and improve the network performance.A technical reference was provided for the operators to deploy the network and resources in the future.